Conditional Conservatism and Debt versus Equity Financing - Goh, Beng Wee; Lim, Chee Yeow; Lobo, Gerald J.; Tong, Yen H. (Contemporary Accounting Research, 2017)
Abstract Extant research suggests that conditional conservatism reduces information asymmetry between a firm and its shareholders as well as its debtholders. However, there is little evidence on whether conditional conservatism reduces information asymmetry differentially for shareholders and debtholders. We use the setting of a firm's choice between equity versus debt when it seeks a significant amount of external financing to examine this research question. We find that when firms raise a significant amount of external financing, the use of equity (versus debt) increases with the level of conservatism. We also find that the reduction in cost of equity associated with conservatism is greater for equity issuers than for debt issuers, but find no such difference when we examine cost of debt. In addition, we find that the positive effect of conservatism on the choice of equity issuance (versus debt issuance) is accentuated when the information asymmetry between the firm and its shareholders is more severe. Overall, our results suggest that conservatism reduces information asymmetry more between firms and shareholders than between firms and debtholders.